CHARACTERIZATION OF MORPHOMETRIC AND BODY WEIGHT BALI CATTLE AND SIMBAL IN BANGKO MERANGIN DISTRICT - A., Zafitra; ., Gushairiyanto; Ediyanto, H.; ., Depison (Majalah Ilmiah Peternakan, 2020)
The purpose of this study was to determine the morphometric characteristics and body weights of bali cattle and simbal cattle as well as to determine the relationship between body measurements with body weights of bali cattle and simbals both male and female. The method used is a survey. The sampling technique was purposive sampling, which is the age of I1 and was not pregnant. The number of samples was 60 bali cattle and 60 simbal cattle. Data collected: body weight, body length, shoulder height, chest circumference, chest depth, chest width, hip height, canon circumference. Data obtained were analyzed using t-test, Principal Component Analysis, and regression and correlation analysis. The results showed that body weight and body measurements of bali cattle were significantly different (P <0,05) from simbal cattle. The body weights of male and female bali cattle were 203.58±18.68 kg, 190.43±11.16 kg lower than those of the simbal male and female respectively, 379.883±49.14 kg, 350.033±31.41 kg The determining factor for the body size of bali cattle and simbals of male and female cattle is chest circumference. The correlation between body measurements with body weight in bali cattle and simbal of male and female cattle is the circumference of the chest. The conclusion of the research is morphometric characteristics and bodyweight of bali cattle are lower than simbals.